Laboratory Evaluation of Femtosecond Laser Lamellar Cuts in Gamma-Irradiated Corneas. Issue 11 (November 2015) - Zhang, Chenxing; Liu, Liang; Tang, Maolong; Li, Yan; Chamberlain, Winston; Huang, David
Abstract : Purpose: To evaluate the stromal interface quality after femtosecond laser full lamellar cuts in gamma-irradiated corneas (VisionGraft sterile cornea) and to determine the limits of the cut depth using the VisionGraft as donor corneas for laser-assisted lamellar anterior keratoplasty. Methods: Fourteen VisionGraft corneas underwent full lamellar cuts using the femtosecond laser. The percent cut depth was 17% to 21% (100 μm, n = 2), 31% to 35% (n = 3), 38% to 40% (n = 3), 45% to 48% (n = 3), and 50% (n = 3) of the total stromal thickness (not including the epithelium). The cap and stromal bed surfaces were imaged with a scanning electron microscope. The quality of cut surfaces was graded by 2 masked observers based on two indices: ridge and roughness. Ridge grading indicated macroscopic irregularity. Roughness grading indicated microscopic irregularity. The grading was done on a subjective integer scale of 1 to 5 (1 = best and 5 = worst), which was used in a previous study of cut quality in fresh corneas. Results: The ridge grading ranged from 1.5 for the shallowest cut to 2.2 for the deepest cut and weakly (r = 0.279) but significantly ( P = 0.037) correlated with the percent cut depth. The roughness grading ranged from 2.63 to 2.56 and showed no trend with the percent cut depth (r = 0.006, P = 0.968). Conclusions: Compared with previously published results of fresh corneas, in which ridge grading exceeded 3 for cuts deeper than 31%, cut quality was better for the VisionGraft. Even at depths up to 48% of the total stromal thickness, ridge grading was not worse than shallow cuts. Thus, gamma-irradiated corneas could provide a smoother interface than do fresh eye bank corneas for laser-assisted lamellar anterior keratoplasty.